(untitled) (Medicine Today, 2014)
Organophosphorus compounds (OPC) poisoning is a major public health problem in low and middle income countries. The incidence varies from country to country depending on easy availability of poison, socio-economic condition and educational background of the people. This study aimed to determine the frequency, outcome and aetiological aspect of OPC poisoning patient admitted in Rangpur medical college hospital. It was a cross sectional study carried out in the department of Medicine, Rangpur medical college hospital from 1st December 2011 to 30th November, 2012. During the study period a total of 703 patients have been studied. The most of the patients were between the age of 18- 40 years (91.9%), male (51.6%), married (71.3%) and from rural areas (67.8%). People of different occupations were involved in OPC poisoning, house-wives were the maximum (33.6%) followed by farmers (31.7%). 92% cases were suicidal and 8% accidental. Familial disharmony was the prime cause (92.3%) of suicidal motive. 88% of the patients were survived and 5% died. OPC poisoning is an important health care problem in our country. Improved awareness, restricting availability and banning more toxic organophosphorus compounds will reduce the incidence of OPC poisoning. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21313 Medicine Today 2014 Vol.26(1): 46-48